KEBEBASAN KEHENDAK (FREE WILL) DAVID RAY GRIFFIN DALAM PERSPEKTIF FILSAFAT AGAMA - , VICTOR DELVY TUTUPARY, Dr. M. Mukhtasar Syamsuddin ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The contemporary human have becoming more aware that freedom is the most primary and integral part that must have existed within us. Freedom has become common sense for modern man. Religion has contributed to the problem of free will, it has also bring serious implication for the problem. Therefore, the study of David Ray Griffinâs Free Will in Philosophy of Religion Perspective aimed to describe the problem of free will in general, and then to explain the main points of Griffinâs thought on this issue, and in the end to analyze his ideas on free will. This study is using qualitative method with literature research on Griffinâs works and some primary and minor books. This research was conducted in three stages, namely: data inventory, data classification, data analysis, and data presentation. The data were analyzed by some methodical devices, such as: interpretation, holistics, historical continuity, and also use heuristics method to analyze Griffinâs conception in Indonesia context. The results of the study are: Firstly, free will is an individual ability to have full control of his or her act and decision without any pressure from others. The problem of free will emerge from the debate between those who believe the very existence of free will and those who against it (determinism). This debate has bring forth two main views: Compatibilism and Incompatibilism. Secondly, Griffinâs ideas consists of process theology and postmodern theology. Process Theology is based on the concept of process, enjoyment, essential relatedness, incarnation, creative self-determination, creative self-expression, novelty, and God-relatedness. Postmodern theology is a critique for two stages of modern view with its dualistic-supernaturalistic and materialistic-atheistic character, and propose a constructive postmodern vision, based on anti-individualistic spirituality, organicism, transformative traditionalism, naturalistic panentheism, and post-patriarchal. Thirdly, Griffinâs conception of free will is divided into cosmology, theology, and axiology freedom. In cosmology freedom, human are creatures with high level of freedom since the dominant poles of the soul in human beings have enabled us to have a free self-determination. In theology freedom, the nature of God that not âall-powerfulâ and the existence of creativity power within human had made us seize a true freedom. In axiology freedom, human have freedom to form the ideal values based on sympathy and pluralism that renounce absolute truth claim, reject religion uniformity, and focus on deep dialogue.